2015
DOI: 10.1007/s11746-015-2735-z
|View full text |Cite
|
Sign up to set email alerts
|

The Updated Bottom Up Solution Applied to Atmospheric Pressure Photoionization and Electrospray Ionization Mass Spectrometry

Abstract: by APPI-MS of vitamin D in the gelcaps gave values of 42.90 ± 0.83 μg, or 1716 ± 33 international units, in good agreement with APCI-MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…That arrangement was used for the LC1/MS4 experiments used to prove the accuracy of the Updated Bottom Up Solution (UBUS) for APCI-MS of soybean oil (Byrdwell, 2015c), and all of the trends in critical ratios from APCI-MS of TAGs were explored in greater detail. In an accompanying publication, it was proved that the UBUS applies equally well to APPI-MS and ESI-MS of TAGs (Byrdwell, 2015b). Chromatograms and mass spectra of those samples, not previously shown, are given in Figs.…”
Section: Quadruple Parallel Mass Spectrometry #1 (Lc1/ms4)mentioning
confidence: 86%
See 1 more Smart Citation
“…That arrangement was used for the LC1/MS4 experiments used to prove the accuracy of the Updated Bottom Up Solution (UBUS) for APCI-MS of soybean oil (Byrdwell, 2015c), and all of the trends in critical ratios from APCI-MS of TAGs were explored in greater detail. In an accompanying publication, it was proved that the UBUS applies equally well to APPI-MS and ESI-MS of TAGs (Byrdwell, 2015b). Chromatograms and mass spectra of those samples, not previously shown, are given in Figs.…”
Section: Quadruple Parallel Mass Spectrometry #1 (Lc1/ms4)mentioning
confidence: 86%
“…However, because the Photospray source was new, it produced a substantial amount of ions from a variety of phthalates (i.e., dibutyl-, dioctyl-, and nonyl, decylphthalates) commonly used as plasticizers. Many of the trends observed in the critical ratios for APCI-MS were observed for APPI-MS, but the range of values of [MH] þ /S[DAG] þ was larger for APPI-MS (Byrdwell, 2015b). …”
Section: Quadruple Parallel Mass Spectrometry #1 (Lc1/ms4)mentioning
confidence: 93%
“…Critical Ratio 1 by APPI-MS followed similar overall trends to APCI-MS (higher ratio for polyunsaturates, values approaching zero for saturates), but exhibited a higher range of values and did not show the distinctly sigmoidal relationship. Critical Ratio 1 for polyunsaturated TAGs was as high as 11.85 by APPI-MS [8], versus a high of 5.20 by APCI-MS [6]. This indicated that APPI-MS showed a greater response to polyunsaturated TAGs than APCI-MS. ESI-MS gave higher values for Critical Ratio 1 in general, but due to the low levels of [DAG] + fragments, the effect of chromatographically unresolved neighboring isobaric TAGs skewed the [MH] + /AE[DAG] + more than the other API-MS techniques.…”
Section: Multiple Parallel Mass Spectrometry and Other Lipidsmentioning
confidence: 92%
“…It also pointed to the real need for the exact same kind of data for atmospheric pressure photoionization (APPI) MS and electrospray ionization (ESI) MS of TAG regioisomers. In the absence of data like that of Holcapek et al [7] for APPI-MS and ESI-MS, Byrdwell tested the effect of using data from APCI-MS for quantification of regioisomers by APPI-MS, ESI-MS, and ESI-MS/MS [8]. It turned out that the regioisomer assignments made by APPI-MS agreed quite well with those by APCI-MS, as shown in Table 1, though quantification varied slightly.…”
Section: Multiple Parallel Mass Spectrometry and Other Lipidsmentioning
confidence: 94%
See 1 more Smart Citation